Repatriating Xhosa music recordings archived at the International Library of African Music (ILAM) and reviving interest in traditional Xhosa music among the youth in Grahamstown - Madiba, Elijah Moleseng (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2019)
This research looks at the feasibility of using repatriation as a tool for the revitalisation of indigenous music within a contemporary South African musical context. Using tracks from the International Library of African Music (ILAM), this investigation presents isiXhosa traditional and indigenous music to a group of musicians from a hip-hop background that would never have had access to this type of music before. The thesis then traces their creative use of the music within their own genres. Speaking to the legacy of the Hugh Tracey collection at ILAM and criticisms that have surfaced, this research also attempts to validate the efforts made by Hugh Tracey in collecting and documenting African music. Themes ranging from understanding the term "tradition" are addressed, as well as other technical terms in the vernacular while also exploring and analysing the results of the repatriation project. Practical issues regarding the sampling of indigenous music were interrogated carefully due to the fact that the complexity of African music was foreign to most of the participants. Their familiarity with the music, or lack thereof, either motivated or ended the musicians' participation in the research project. An in-depth analysis of the results of the musicians' interaction with the music is presented where this study finds, at the heart of this research, that the musicians performed as agents who easily took to revitalising the music.
Keywords: International Library of African Music; Xhosa (African people) -- Music; Sound recordings in ethnomusicology -- South Africa; Ethnomusicology -- South Africa -- Makhanda; Cultural property -- Repatriation -- South Africa -- Makhanda; Rap musicians -- South Africa -- Makhanda